Experimental study and mechanism analysis on improving the workability of metakaolin-based geopolymers using superplasticizer - Zhang, Genhe; Cao, Feng; Li, Taotao; Sun, Chao; Yao, Linhao; Chang, Yongqi; Su, Wenbin; Chen, Hao; Guo, Wei; Wu, Rui; Ma, Biao (Frontiers in Materials, 2026)
Metakaolin-based geopolymer is considered a potential alternative to traditional cement materials; however, its fresh paste typically suffers from high viscosity and poor workability. To evaluate the effect of superplasticizers, this study first optimized the basic mix proportions of alkali-activated metakaolin geopolymer through orthogonal testing. The influences of five superplasticizers—melamine, sodium lignosulfonate, naphthalene-based, polycarboxylate, and KH-550 at varying dosages were then examined in terms of flowability and compressive strength. The mechanisms of superplasticizer action were further investigated by means of physical stability assessment, Fourier-transform infrared spectroscopy (FTIR), surface tension, and zeta potential testing. The results indicate that the optimal mix design for the metakaolin-based geopolymer is achieved with a silicate modulus of 0.9, a liquid-to-solid ratio of 0.75, and a silica fume content of 15%, leading to a 28-day compressive strength of 58.8 MPa and a flow diameter of 132 mm. Compared with other superplasticizer, sodium lignosulfonate exhibited superior water-reducing efficiency and stability, while its adverse effect on compressive strength was acceptable. Balancing workability and strength requirements, the optimal dosage was determined to be 1.5%. Mechanism analysis further revealed that superplasticizer can enhance electrostatic repulsion between particles, thereby improving the flowability of metakaolin-based geopolymers. This research provides a viable pathway for preparing metakaolin-based geopolymers with superior mechanical properties and workability.